2011
DOI: 10.1038/hr.2011.77
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular repolarization before and after treatment in patients with secondary hypertension due to renal-artery stenosis and primary aldosteronism

Abstract: A prolonged QT interval is a risk factor for ischemic heart disease in hypertensive subjects. Patients with renal-artery stenosis and primary aldosteronism (PA) are at increased risk of cardiovascular events. The objective of the present study was to evaluate the QT interval in patients with renovascular hypertension (RV) and PA before and after treatment. A total of 24 patients with RV and 38 with PA were studied; 89 patients with essential hypertension (EH) served as control group. Corrected QT intervals (QT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It is now well established that, compared to patients with essential hypertension, QTc interval is prolonged in patients with hyperaldosteronism (primary aldosteronism or Conn's adenoma), with a high proportion of patients experiencing QTc values higher than 440 ms (Matsumura, K., et al, 2005;Maule, S., et al, 2011). Several explanations may be proposed.…”
Section: Impact Of Aldosterone a Non-sex Steroid Hormone On Cardiacmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now well established that, compared to patients with essential hypertension, QTc interval is prolonged in patients with hyperaldosteronism (primary aldosteronism or Conn's adenoma), with a high proportion of patients experiencing QTc values higher than 440 ms (Matsumura, K., et al, 2005;Maule, S., et al, 2011). Several explanations may be proposed.…”
Section: Impact Of Aldosterone a Non-sex Steroid Hormone On Cardiacmentioning
confidence: 99%
“…Several explanations may be proposed. First, the presence of higher blood pressure levels, due to the increased aldosterone secretion, might contribute to QT interval prolongation in these patients (Maule, S., et al, 2011). Indeed, hyperaldosteronism is associated with high blood pressure levels and left ventricular hypertrophy (Milliez, P., et al, 2005) and patients with left ventricular hypertrophy exhibit prolonged QT interval (Dritsas, A., et al, 1992;Martin, A.B., et al, 1994) possibly as a consequence of down-regulation of the human ether-a-go-go related gene expression (Hu, C., et al, 2011).…”
Section: Impact Of Aldosterone a Non-sex Steroid Hormone On Cardiacmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that PA patients display an increased prevalence of long QT, at least in part independent from potassium levels [ 60 ] , which is reverted after adrenalectomy or therapy with spironolactone [ 61 ] .…”
Section: Clinical Features and Complications Of Pamentioning
confidence: 99%
“…Of that group, 16 were revascularized and tolerated re-introduction of these agents without difficulty (14). A separate report indicated that patients with RVH had prolonged QT intervals during medical therapy as compared to essential hypertension (17). Twenty-four of these underwent renal artery stenting with normalization of the QT interval.…”
Section: Medical Therapy Of Hypertension With Renovascular Diseasementioning
confidence: 99%